Body and Distance: Learning Connectedness and Belonging from Modern Movement – Case Study New Belgrade - Kordić, Milena; Zorić, Ana; Todorović, Dejan; Mrlješ, Rade (Docomomo Journal, 2025)
The boundaries between the private, shared, and public spheres are challenged in completely new ways in times of pandemics, and we need new strategies to redefine them. During pandemics, prevailing requests for physical distancing in the urban space eliminated the programs from everyday lives that all have included social interaction, exchange, and connectedness. So, the request for physical distance caused actual social distance, which further brought new problems of solitude and isolation to the individual in the urban environment. How can architecture and design help to provide physical distance while maintaining social closeness, empathy, and solidarity in cities? Modern Movement heritage, especially in the countries that were under socialist political regimes, teaches us that shared spaces, collective spaces as part of public spaces, are places in which community is being formed and strengthened, where new forms of affiliation and belonging arise. The socialist paradigm emphasizes the importance of open public spaces within the residential zone as places for maintaining physical activity and health, as well as social interaction. By examining the modernist development of New Belgrade through a comparative analysis of two case studies focusing on the same area—specifically, the blocks known as Blok 22—we can reinvigorate the concept of the connection between the interior and shared spaces. The specific values of open spaces within the residential modernist block have proven to be particularly important during times of crisis, such as the COVID-19 pandemic, especially regarding the degree of connectedness or separation between private and public spaces. During the pandemic, a student workshop was organized, resulting in projects that offered new architectural scenarios and models for using shared spaces in a residential block. These models allowed for the preservation of physical distance among individuals while enabling social interactions and even the emergence of new programs as an extension of housing. The workshop highlighted the importance of this concept not only during crises but also in contemporary living conditions in large cities, which struggle with issues of alienation and loneliness.